Penerapan Sanksi Hukum Terhadap Pelaku Pencabutan Penjor Sebagai Rangkaian Upacara Galungan Pada Umat Beragama Hindu di Desa Adat Taro Kelod Kabupaten Gianyar - Kadek Teddy Hendrawan; I Wayan Wesna Astara; Diah Gayatri Sudibya (Jurnal Preferensi Hukum, 2024)
Indonesia as a rule-of-law country has statutory regulations, relating to criminal sanctions and sentencing. In addition, some laws apply throughout the area called Customary Law, including in Bali. Perpetrators of the destruction of goods as well as religious blasphemy can be punished with the general criminal code or, in comparison with the Applicable Customary Law. This research examines 2 things: 1) How is the existence of the Hindu religious community in carrying out its obligations and legal protection for Hindu religious people in terms of Human Rights? and 2) What is the application of legal sanctions in the event of the revocation of the penjor for Hindus in the Taro Kelod Village area, Gianyar Regency? The method used in this research is Empirical Research. The purpose of this research is to emphasize the study of the protection of penjor removal victims in Taro Kelod Village, Gianyar. With the results of the study showing that a person deliberately destroys goods together and harms someone, it is possible to be subject to Article 170 paragraph (1) and Article 156A letter A concerning religious blasphemy, because the penjor being revoked is a sacred symbol and has religious meaning for Hindus.